Equivalent current models for magnets characterization. Issue 5 (7th September 2015) - Bonito Oliva, Alessandro; Chiariello, Andrea Gaetano; Formisano, Alessandro; Martone, Raffaele; Portone, Alfredo; Testoni, Pietro
Abstract : Purpose: – The purpose of this paper is to analyze the impact of different current representation models in the high field magnets characterization. Inverse source methodology used for current reconstruction is discussed. The regularizing effect of successive field map computation in different regions is also assessed. Design/methodology/approach: – Under suitable hypotheses, the resulting inverse source problem is linear, and different current representation bases are used to assemble different matrices. Properties of matrices are then assesses using SVD. The following field computation problem is also formulated using a projection matrix, and the properties of combined matrix operators are analyzed and compared to the inversion matrix. Findings: – The characteristics of the inverse matrix depend on the choice of the current representation basis, but in any case the application of the further projection matrix has a relevant regularizing effect. Research limitations/implications: – The method is intrinsically tied to the linearity assumption, and the regularizing effect of the projection operator is stronger for further field regions. Practical implications: – The accuracy in the current reconstruction procedure can be reduced if data will be used only to compute field in distant regions. Originality/value: – The paper casts the problem of field computation in distant regions from magnetic measurements in the language of direct and inverse operators, allowing to assess its properties and fine tune the procedure parameters to achieve satisfactory results with minimum effort.